Benthic invertebrates in the headwaters of the Wye and Severn: effects of forestry and clear-felling - J. H. R. Gee; B. D. Smith (Hydrology and Earth System Sciences, 1997)
Invertebrate communities were recorded in three surveys between 1974 and 1994 of headwaters of the Wye and Severn at Plynlimon: the Afon Gwy (unforested), the Afon Hore (initially forested) and the Afon Hafren (forested throughout). The data cover periods before and after the clear-felling of a large area of coniferous forest in the catchment of the Hore. All three streams contained invertebrates characteristic of acidic, upland conditions and had similar species richness. Differences in assemblage composition within streams between surveys could be related to differences in method or timing of sampling. All assemblages were dominated by Insecta, particularly Plecoptera and Diptera, whereas Ephemeroptera, Moilusca, Crustacca and some families of Trichoptera (notably Hydropsychidae and Philopotamidae) were poorly represented. The forested streams (Hafren and Hore) contained similar assemblages which differed from those in the unforested stream (Gwy) in containing lower densities of Ephemeroptera and Oligochacta and much higher densities of nemourid and leuctrid Plecoptera. Clear-felling of the Hore catchment resulted in changes in physical and chemical conditions (including a reduction of stream pH, and increases in dissolved aluminium concentration and summer water temperature) but no related change in the invertebrate assemblage. The apparent failure of invertebrates to respond as expected to substantial changes in local environmental conditions may reflect either a lack of understanding of causal links between invertebrates and environmental factors, or the over-riding influence of the dynamics of recruitment to populations.